2023
DOI: 10.6007/ijarems/v12-i1/15749
|View full text |Cite
|
Sign up to set email alerts
|

Does Financial Liberalization Cause Economic Growth? A Meta-analysis Review

Abstract: This study examines the impact of financial liberalization on developing countries' growth rates and the relationship between the variables using the fixed effects least squares approach for five developing countries from 1990 to 2021. Based on the results, financial liberalization and economic freedom are the driving factors underlying economic growth in five Asean members (Thailand, Singapore, Indonesia, Malaysia, and the Philippines). Secondly, financial liberalization puts the financial system at risk, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Prior studies (Orji et al, 2015;Haruna & Abu Bakar, 2021;Kudaisi et al, 2021) reported that increased liberalization of an economy tends to accelerate economic growth, particularly through greater resource augmentation and mobilization and higher degree of greater competition. Financial liberalization involves activities that eliminate constraints put on the financial and banking industries (Latib & Mohamad, 2023). These constraints in developing countries tends to result in high consumption, low savings and low investment, leading to distortion in the market and inhibiting economic growth (Adam, 2020).…”
Section: Financial Liberalizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies (Orji et al, 2015;Haruna & Abu Bakar, 2021;Kudaisi et al, 2021) reported that increased liberalization of an economy tends to accelerate economic growth, particularly through greater resource augmentation and mobilization and higher degree of greater competition. Financial liberalization involves activities that eliminate constraints put on the financial and banking industries (Latib & Mohamad, 2023). These constraints in developing countries tends to result in high consumption, low savings and low investment, leading to distortion in the market and inhibiting economic growth (Adam, 2020).…”
Section: Financial Liberalizationmentioning
confidence: 99%
“…The traditional trade theory asserts that higher levels of trade bring about improvement in the economy (Farahane & Heshmati, 2020). A country's import and export activities provide beneficial outcomes in the form of expansion in production, support to the local business, expansion in job opportunities, and increase in national income which directly contribute to the economy (Latib & Mohamad, 2023). Prior studies (Keho, 2017; Oppong-Baah et al, 2022; Hungu, 2023) assert that trade openness positively impacts the financial liberalization and economic growth nexus.…”
Section: Trade Opennessmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is increasingly apparent, as numerous economies have abandoned the practice of financial repression and instead adopted policies of financial liberalization. Sulaiman, Oke, and Azeez (2012) argued that in many developing nations, financial repression was the norm until the transition to financial liberalization occurred. Financial repression introduces regulations that lower interest rates, leading to lower savings and declining investment (McKinnon, 1973).…”
Section: Background To the Studymentioning
confidence: 99%
“…It is sufficient to say that a preponderance of these studies focused mainly on the impact of financial openness on economic growth. For country-specific studies, Sulaiman et al (2012) revealed that financial openness improved economic growth in Nigeria. This result was corroborated with a study by Anthony, Ogbuabor, and Anthony-Orji (2015) which observed that financial liberalization and private investment had positive and significant impact on economic growth in Nigeria.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%